Clinical and Business Intelligence: Why It's Important to Your Pharmacy. Issue 7 (July 2016) - Pinto, Brian; Fox, Brent I.
According to the Healthcare Information Management and Systems Society, "Clinical & Business Intelligence (C&BI) is the use and analysis of data captured in the healthcare setting to directly inform decision-making" (http://www.himss.org/library/clinical-business-intelligence ). Some say that it is the right information given to the right person at the right time in the right way. No matter how you define it, the fact remains that timely access, synthesis, and visualization of clinical data have become key to how health professionals make patient care decisions and improve care delivery.